COMBINED ACETYLSALICYLIC ACID TABLETS TECHNOLOGY - A. V. Simonyan; A. A. Salamatov; M. A. Simonyan; A. N. Kozhanova; N. O. Maraikina; J. S. Popova (Разработка и регистрация лекарственных средств)
It was developed combined dosage form - tablets, each containing 0,25 g of acetylsalicylic acid and 0,1 g of cycvalon that meet the requirements of the State Pharmacopeia XII and State Pharmacopeia XIII. Addition of cycvalon allows to prepare tablets at a low pressure, which will reduce labor, energy costs of manufacture of tablets and to increase the service life of the press tool.